TRANSLATING THEORY INTO PRACTICE: THE GENDER AND DEVELOPMENT TRAINING EVALUATIONS USING THE KIRKPATRICK’S MODEL - Ariel E. San Jose (International Conference on Social and Islamic Studies, 2021)
The Philippines Commission on Higher Education (CHED) made a landmark policy declaration when it released Memorandum Order (CMO) No. 01, series of 2015, or "Establishing the Policies and Guidelines on Gender and Development in CHED and Higher Educational Institutions" which seeks to institutionalize gender equality, responsiveness, and sensitivity in all facets of Philippine higher education." In response to this CMO, this study was conducted not only to evaluate the participants’ reactions, learning, behavioral change, and applications of the Gender and Development (GAD) training they attended but also to obtain suggestions for the improvement of succeeding training. Mixed method was used. Random sampling was applied in selecting the participants. Twenty-eight teachers and staff were involved. Convergence of data and information revealed that GAD training brought significant and favorable benefits to the participants. However, the participants were keen on the qualifications of the resource speakers; mediocre attendees; repetition of topics; involvement of other stakeholders; planning and organizing of the training. It also revealed that the participants highly regarded the applicability of the concepts presented in the GAD training. It was suggested that GAD organizers need to strategize and make thorough planning by looking at every detail of the training.